2019
DOI: 10.1021/acs.biochem.9b00360
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Nonribosomal Peptide Synthetases in the Biosynthesis of the Pseudomonas virulence factor

Abstract: The Pseudomonas virulence factor (pvf) biosynthetic operon has been implicated in bacterial virulence and signaling. We identified 308 bacterial strains containing pvf homologues that likely produce signaling molecules with distinct structures and biological activities. Several homologues of the nonribosomal peptide synthetase (NRPS), PvfC, were biochemically characterized and shown to activate L-Val or L-Leu. The amino acid selectivity of PvfC and its homologues likely direct pvf signaling activity. We explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…In view of the structures of 2 and 1 , it was hypothesized that l ‐valine ( 3 ) was the substrate for their biosyntheses. Our suggestion is in agreement with a recent study performed on PvfC, a homologue of HamD initially discovered in a Pseudomonas entomophila strain . Li and co‐workers identified the key residues of the active site, and demonstrated through bioinformatics and experimental studies that 3 is the initial substrate of the PvfC NRPS.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…In view of the structures of 2 and 1 , it was hypothesized that l ‐valine ( 3 ) was the substrate for their biosyntheses. Our suggestion is in agreement with a recent study performed on PvfC, a homologue of HamD initially discovered in a Pseudomonas entomophila strain . Li and co‐workers identified the key residues of the active site, and demonstrated through bioinformatics and experimental studies that 3 is the initial substrate of the PvfC NRPS.…”
Section: Methodssupporting
confidence: 92%
“…However, because of the structure of fragin, we proposed that either valine or leucine would be the substrate of the HamD adenylation domain. This is supported by recently published data that identified valine as the amino acid substrate of PvfC, which has in its adenylation domain a ten‐amino‐acid code identical to that in HamD . To test valine incorporation into fragin, feeding experiments were performed with [U‐ 13 C 5 ]‐ l ‐valine ( 4 , Scheme ) and the supernatant was analyzed by HRMS.…”
Section: Methodsmentioning
confidence: 57%
“…This result indicated that it may be the indigenous signal produced by Pss ( Figure 2C) and is also in line with a bioinformatics analysis of the substrate specificity of the adenylation domain of MgoA. 37 To increase the sensitivity of our detection strategy, we developed a UHPLC-MS/MS method using our synthetic standard. An extraction was performed on two liters culture media containing Pss and its ΔmgoA mutant.…”
Section: Inactivation Of Leudiazensupporting
confidence: 78%
“…27,34 Furthermore, in 2018, Li and coworkers engineered a P. entomophila strain to overexpress the pvf cluster leading to the production of three N-oxide metabolites 35 and they investigated the role of the N-oxygenase in the biosynthesis of valdiazen (1). 36 In a follow up study, the same research group investigated the substrate specificity of the NRPS domain of PvfC and its homologs MgoA and HamD in different proteobacteria and concluded that at least two types of signaling molecules are produced by the different strains 37…”
Section: Introductionmentioning
confidence: 99%
“…We sought to determine the role of PvfB in (d)PNO biosynthesis. Valine is incorporated into (d)PNOs by PvfC from P. entomophila L48 (Figure 1 B), [1,4] but PvfB does not modify free valine or 2,5-diisopropyl pyrazine (Supporting Information, Figure S8), thus, we hypothesized that PvfB directly N-oxygenates PvfC-tethered valine. We used liquid chromatography-coupled high-resolution mass spectrometry (LC-HRMS) to study the activity of PvfB on PvfC-tethered valine.…”
mentioning
confidence: 99%